1999
DOI: 10.1210/mend.13.5.0281
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activities of the Orphan Nuclear Receptor ERRα (Estrogen Receptor-Related Receptor-α)

Abstract: Estrogen receptor-related receptor alpha (ERR alpha) is an orphan nuclear receptor closely related to the estrogen receptor (ER), whose expression covers various stages of embryonic development and persists in certain adult tissues. We show that ERR alpha binds as a homodimer on a specific target sequence, the SFRE (SF-1 response element), already known to respond to the orphan nuclear receptor SF-1. Target sequences that are related to the SFRE and that discriminate between ERR alpha and SF-1 were identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 35 publications
(58 reference statements)
4
38
0
Order By: Relevance
“…In EMSA, ERR␣1 formed two complexes on either element, whereas ER␣ formed only one complex with SFRE. Homodimerization of ER␣ was well documented with EREs (18), and a recent report also showed homodimer binding with SFRE (44). Therefore, the single complex of ER␣-SFRE in EMSA (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In EMSA, ERR␣1 formed two complexes on either element, whereas ER␣ formed only one complex with SFRE. Homodimerization of ER␣ was well documented with EREs (18), and a recent report also showed homodimer binding with SFRE (44). Therefore, the single complex of ER␣-SFRE in EMSA (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…These findings show a complicated picture of mechanisms of estrogen action and make the interpretation of estrogen response in different cell types difficult. In contrast to the synthetic SFRE, which required multiple copies to confer ERR␣1 response (38,44), a single copy of the lactoferrin SFRE is functioning in our current study (Fig. 2).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, whereas ERs are ligand-activated receptors, ERRs are constitutively active (13)(14)(15)(16), and a structural study confirmed that the ERR␥ LBD can adopt a transcriptionally active conformation and interact with the steroid receptor coactivator 1 (SRC-1) in the absence of any ligand (12). Together, these observations suggest that ERRs are ligand-independent activators of transcription whose activation potential may rather be determined by the presence of transcriptional coactivators (17)(18)(19)(20).…”
mentioning
confidence: 92%